Analisis Rasio Keuangan Pada KSP Kopdit Suru Pudi Koting - Gracela Pinkan Antou; Yuliana Anggreani Dua Delang Kolit; Thadeus Fransesco Quelmo Patty; Elisabeth Yessi Da Rato (Jurnal Projemen UNIPA, 2025)
Financial ratio analysis is essential for cooperatives to assess their financial performance over each period. This research aims to determine the values of liquidity ratios, solvency ratios, and profitability ratios at KSP Kopdit Suru Pudi Koting from 2020 to 2023. This study employs a quantitative approach. The type of data used is secondary data. The data analysis method employed is the use of financial ratios. The research findings indicate that: (1) The liquidity ratio measured by the Current Ratio at KSP Kopdit Suru Pudi from 2020 to 2023 fluctuated, tending to decline, and was in the 'Healthy' category (2020/2021) and the 'Unhealthy' category (2022/2023). (2) The value of the Solvency Ratio calculated using the Debt to Asset Ratio (DAR) and the Debt to Equity Ratio (DER) at KSP Suru Pudi for the period 2020-2023 fluctuates and tends to increase, falling within the 'Healthy' criteria. (3) The profitability ratios calculated using Return on Assets (ROA) and Return on Equity (ROE) at KSP Suru Pudi for the period 2020-2023 tend to decrease, falling within the 'Unhealthy' criteria.